Meta-analysis of randomized controlled trials examining the safety and efficacy of bempedoic acid. (11th May 2022) - Borgatta, L; Sturts, A; Zaman, N; Grewal, S; Nudy, M
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: Bempedoic acid (BA), an inhibitor of ATP citrate lyase, has emerged as a new therapy for patients with dyslipidemia. The objective of this study was to perform a meta-analysis of BA's safety and cholesterol lowering efficacy. Methods: A meta-analysis was performed using RCTs testing the safety and efficacy of BA versus placebo. The primary analysis calculated the odds ratio (OR) and 95% confidence interval (CI) of any adverse events, muscular-related AEs including myopathy, muscle weakness, and myalgias, as well as serious AEs as self-defined by the individual RCT. Additionally, we evaluated the mean difference (MD) and CI of low density lipoprotein-cholesterol (LDL-C), non-high density lipoprotein-cholesterol (non-HDL-C), total cholesterol (TC), and apolipoprotein B (ApoB) at 12 weeks, as well as LDL-C at 24 weeks of BA use as compared to placebo. Results: Four RCTs were identified comparing BA to placebo. There was no increased risk of any AE [OR 1.04; 95%CI 0.89, 1.22], serious AE [OR 1.07; 95%CI 0.87, 1.34], or muscular-related AE [OR 1.25; 95%CI 0.98, 1.58] with BA use compared to placebo. BA resulted in a significant reduction in LDL-C [MD -21.06; 95%CI -24.49, -17.62], TC [MD -16.02; 95%CI -19.09, -12.93], non-HDL-C [MD -17.84; 95%CI -21.34, -14.34], and ApoB [MD -14.19; 95%CI -17.18, -11.21] at 12 weeks, and LDL-C at 24 weeks [MD -16.42; 95%CI -18.15, -14.69] compared to placebo. Conclusion: In this meta-analysis testing BA versus placebo, BA significantly reduced levels of LDL-C, TC, non-HDL-C, and ApoB at 12 weeks and LDL-C at 24 weeks, and was not associated with an increased risk of any AE, muscular-related AE or serious AE. Further studies with longer time of follow up are needed to confirm the safety and long term cholesterol effects of BA.